Les modillons de terre cuite de la basilique de Saint-Martin de Tours (Indre-et-Loire) et de l’église abbatiale Sainte-Marie de Saint-Benoît-sur-Loire (Loiret) : l’expression de deux groupes ligériens - Sébastien Jesset (Revue Archéologique du Centre de la France)
Today, Tours and Saint-Benoît-sur-Loire preserve the two most important collections of terracotta modillions from the Early Middle Ages of the Middle Loire valley, excluding the city of Orléans where these construction materials, were found in one, two or three copies on more than a dozen sites, and Saran a well-known village of potters for the Early Middle Ages.The interest of the collections of Tours and Saint-Benoît lies moreover in places of highly symbolic value, which are the basilica of Saint-Martin on one hand and the abbey church of Sainte-Marie on the other hand.Beyond a simple difference in the actual shaping of the modillions (the Touraine specimens being molded and those of the Orléanais sculpted), these two series of objects are the expression of two different conceptions of the modular cornice, probably a cultural heritage from Antiquity.